2020
DOI: 10.1155/2020/8872593
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Target Prediction and Docking Verification of Hua‐Feng‐Dan in Stroke Based on Network Pharmacology

Abstract: Objective. Hua-Feng-Dan (HFD) is a Chinese medicine for stroke. This study is to predict and verify potential molecular targets and pathways of HFD against stroke using network pharmacology. Methods. The TCMSP database and TCMID were used to search for the active ingredients of HFD, and GeneCards and DrugBank databases were used to search for stroke-related target genes to construct the “component-target-disease” by Cytoscape 3.7.1, which was further filtered by MCODE to build a core network. The STRING databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…On the other hand, the downregulation of the PI3K inhibitor LY294002 [47], p38 MAPK inhibitor SB203580 [48], and MEK1/2 inhibitor U0126 [49] further facilitated the activation of these adaptive responses. A network pharmacology analysis of anti-stroke effects of Hua-Feng-Dan revealed potential molecular targets [7], and some of the regulated molecules coincide with the adaptive responses induced by Hua-Feng-Dan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the downregulation of the PI3K inhibitor LY294002 [47], p38 MAPK inhibitor SB203580 [48], and MEK1/2 inhibitor U0126 [49] further facilitated the activation of these adaptive responses. A network pharmacology analysis of anti-stroke effects of Hua-Feng-Dan revealed potential molecular targets [7], and some of the regulated molecules coincide with the adaptive responses induced by Hua-Feng-Dan.…”
Section: Discussionmentioning
confidence: 99%
“…Hua-Feng-Dan and its "Guide Drug" Yaomu Hua-Feng-Dan (HFD) and its Guide Drug Yaomu (YM) were provided by Hua-Feng-Dan Pharmaceutical Co. (Guizhou, China). Yaomu is the most important part of the traditional medicine Hua-Feng-Dan [15], and fermented for three months before using as the "Guide Drug" to make Hua-Feng-Dan with other herbs, animal-based products, and minerals as listed in Introduction and reported previously [1,[5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical ingredients of PT were gathered from TCMSP database ( http://old.tcmsp-e.com/tcmsp.php ). In order to select the ingredients, which have better pharmacokinetic properties and oral bioavailability in vivo, the ingredients were filtrated by suggested criterion in TCMSP database, and the ingredients whose drug-likeness (DL) ≥0.18 and oral bioavailability (OB) ≥30% were regarded as putative major ingredients and retained [ 16 ]. Additionally, the SMILES number of ingredients obtained from PubChem database was imported into the SwissTargetPrediction database through Probability ∗ >0 to select the predicted targets.…”
Section: Methodsmentioning
confidence: 99%
“…), animal-based products ( Moschus berezovskii Flerov (Shexiang); Buthus martensii Karsch (Quanxie), Bombyx mori Linnaeus (Jiangcan), and other minerals (Borax; Borneolum Syntheticum) ( Liu et al, 2018 ). Network pharmacology has found that β-sitosterol, luteolin, baicalein, and wogoni are potential active ingredients ( Yang et al, 2020 ), but experimental verification is required. We have demonstrated the protective effects of Hua-Feng-Dan against LPS plus MPTP-induced Parkinson’s disease (PD) mouse model ( Hu et al, 2020 ), and LPS plus rotenone-induced PD rat model ( Chen et al, 2020 ), and identified that cinnabar and realgar are two active ingredients in the recipe both in LPS-induced neuroinflammation in rat midbrain neuron–glia cocultures ( Zhang et al, 2012a ) and in LPS plus rotenone-induced dopaminergic neuron loss in rats ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%